Evaluation of the Productive Age Health Services Implementation in Bekasi City - Muhammad, Khansa Fatihah; Achadi, Anhari (Journal of Public Health for Tropical and Coastal Region, 2024)
AbstractIntroduction: Productive-age health services in Bekasi have not reached the standard target of 100%. By 2023, the percentage of productive-age health services was 27.96%. Therefore, this study aims to conduct a formative evaluation of the implementation of productive-age health services in Bekasi City based on the logical framework, especially in the Mustika Jaya Community Health Centre and Rawa Tembaga Community Health Centre.Methods: This was a qualitative study with a case study design conducted over two weeks. The data were collected through in-depth interviews. The informants were selected based on the principles of appropriateness and adequacy.Results: The study found that while health equipment, funding, and human resources are generally adequate, challenges persist in data management and human resource capacity-building. The recording and reporting system, SI-PTM, requires improvement in integrated data management. There is a need for increased awareness among the target population through innovative outreach programmes. The short-term goal of productive-age health services aligns with the long-term vision outlined in RPJMD.Conclusion:  The implementation of productive-age health services in Bekasi City requires further improvement to achieve the 100% minimum health service standard. Community Health Centers in Bekasi City can enhance cross-program and cross-sectoral collaboration with productive-age health services, increase people's awareness with an innovative outreach, and ensure that human resources in productive-age health services receive training.